Measurement of salusin-? without the addition of NP-40 or Tween-20 in coronary slow-flow phenomenon - Aydin, Suna; Yardim, Meltem; Akkoc, Ramazan Fazil (Turkish Soc Cardiology, 2020)
[Abstract Not Available]